Complexos contendo bases de Schiff simétricas e não-simétricas: I – Complexos mono- e trinucleares de Níquel(II) e de Cobre(II) com ligantes do tipo salen para oxidação de catecóis; II – Complexos de Zinco(II) com aminotroponiminatos para polimerizações - Bucalon, Daniel Haguihara (2018)
In this work two topics involving symmetric and non-symmetric Schiff bases were investigated. In the first part, the mono- and trinuclear complexes of nickel (II) and copper (II) were studied as catalysts in the oxidation reaction of 3,5-di-tert-butyl-catechol. A variety of structures with yields above 58% were synthesized and characterized. Regarding the structures and properties obtained, the characterization data indicate remarkable differences between the mono- and trinuclear complexes. The series of structures allowed the possibility of evaluating and correlating the stereo and electronic effects with the catalytic activities of the compounds. The nickel (II) and copper (II) trinuclear complexes showed higher catalytic efficiency than their respective mononuclear complexes. Within the series of copper (II) trinuclear complexes, the 3-ethoxy substitution compound and two methyl groups [Cu(Cu(3OEtsaldmen)}2(ClO4)2] were found to be the most efficient. It has been found that there was an increase in catalytic efficiency with the change of substituents on the aromatic ring with the sequence -OH <-H <-OMe <-OEt. Furthermore, in general, by analyzing the effect of the methyl substituents close to one of the imines, the following order to the catalytic efficiency was found: -H; -H < -H;-CH3 < -CH3;-CH3, but depending on the substituent at the postion 3 on the ring, this effect was more or less pronounced. In the second part, three new complexes of type [Zn(ATI){N (SiMe3)2}] were synthesized, characterized and tested tested in the ring-opening polymerization of the lactones β-rac-butyrolactone and rac-lactide. The ligands, with two of them unknown in the literature, were readily obtained via a three-step synthesis from tropolone. The influence of the varying metallacycle ring size on the polymerization was evaluated. In situ IR measurements indicate a higher catalytic activity of the novel aminotroponiminate complexes for β-rac-butyrolactone compared with the β-diiminate system. The activity and degree of control were further improved by an in situ generated alkoxy initiating group generated after the addition of 2-propanol. An enhanced initiator efficiency allowed the synthesis of polymers with controlled molecular weights and narrow polydispersities. Furthermore, complexes with ethyl and isopropyl groups exhibited a high activity in the ring-opening polymerization of rac-lactide. Hereby, reaction time and initiator efficiency could also be optimized at a higher temperature or by the addition of 2-propanol.